Aberrant proteins expressed in skin fibroblasts of Parkinson's disease patients carrying heterozygous variants of glucocerebrosidase and parkin genes - Sawangareetrakul, Phannee (Biomed Rep, 2021)
Parkinson's disease (PD) is a neurodegenerative disorder that affects movement, and its development is associated with environmental and genetic factors. Genetic variants in GBA and PARK2 are important risk factors implicated in the development of PD; however, their precise roles have yet to be elucidated. The present study aimed to identify and analyse proteins from the skin fibroblasts of patients with PD carrying heterozygous GBA and PARK2 variants, and from healthy controls. Liquid chromatography coupled with tandem mass spectrometry and label-free quantitative proteomics were performed to identify and compare differential protein expression levels. Moreover, protein-protein interaction networks were assessed using Search Tool for Retrieval of Interacting Genes analysis. Using these proteomic approaches, 122 and 119 differentially expressed proteins from skin fibroblasts of patients with PD carrying heterozygous GBA and PARK2 variants, respectively, were identified and compared. According to the results of protein-protein interaction and Gene Ontology analyses, 14 proteins involved in the negative regulation of macromolecules and mRNA metabolic processes, and protein targeting to the membrane exhibited the largest degree of differential expression in the fibroblasts of patients with PD with a GBA variant, whereas 20 proteins involved in the regulation of biological quality, NAD metabolic process and cytoskeletal organization exhibited the largest degree of differential expression in the fibroblasts of patients with PD with a PARK2 variant. Among these, the expression levels of annexin A2 and tubulin β chain, were most strongly upregulated in the fibroblasts of patients with GBA-PD and PARK2-PD, respectively. Other predominantly expressed proteins were confirmed by western blotting, and the results were consistent with those of the quantitative proteomic analysis. Collectively, the results of the present study demonstrated that the proteomic patterns of fibroblasts of patients with PD carrying heterozygous GBA and PARK2 variants are different and unique. Aberrant expression of the proteins affected by these variants may reflect physiological changes that also occur in neurons, resulting in PD development and progression.